A bi-level charging management approach for electric truck charging station considering power losses - Gokcek, Tayfur; Turan, Mehmet Tan; Ates, Yavuz; Arabul, Ahmet Yigit (Tubitak Scientific & Technological Research Council Turkey, 2022)
This article presents an optimized heavy duty electric truck charging station (ETCS) design based on bi-level mixed integer linear programming. Electric truck parameters are integrated with the grid model and charging sequences are firstly formulated to optimize charging stages. As the second level of the optimization stage, line losses are aimed to be minimized for the charging station. ETCS model is obtained from actual parameters of the Istanbul Muratbey Customs zone which is one of the busiest customs zone in Europe and an ideal location for ETCS application in the future. The ETCS is equipped with roof type photovoltaic (PV) modules and the capacity of the PV generation is determined in accordance with the actual data of the customs zone buildings. The PV generated power is integrated with electric truck demand which varies in daytime based on hourly intervals along with the seasonal impact. Ultimately, an optimized ETCS model is presented including PV generated power to reduce line losses and CO2 emission along with optimized charging sequences for ETCS with huge power consumption. The proposed model represents the reduction of line losses along with the obtained environmental and economic benefits.
Keywords: i-level optimization; charging management; electrical truck; power losses; voltage profile; VEHICLES; IMPACT; LIFE; EMISSIONS; FREIGHT; DESIGN; SYSTEM; COSTS; Computer Science; Engineering